Successful embolization of mesenteric hematoma following blunt trauma: A case report - Rika Yoshida; Hisatoshi Araki; Yuki Komatsubara; Yuka Ishikura; Mitsunari Maruyama; Shinji Ando; Megumi Nakamura; Takeshi Yoshizako; Akihiko Kidani; Yasushi Kaji (Radiology Case Reports)
Mesenteric injuries are rare, occurring in approximately 1% of all blunt trauma cases. Herein, we report the case of a man in his 70s who sustained an isolated mesenteric hematoma following blunt abdominal trauma from a detached tire. The hematoma was successfully managed with transcatheter arterial embolization (TAE), avoiding the need for invasive surgery and preventing bowel ischemia. This case highlights the importance of early diagnosis and prompt intervention with TAE in hemodynamically stable patients with mesenteric injuries.